Ensemble-averaged Rabi oscillations in a ferromagnetic CoFeB film - Amir Capua (Nature Portfolio, 2017)
External driving of Rabi oscillations is a first step in the coherent manipulation of spin systems. Here the authors use ultrafast optical pulses to produce classical Rabi oscillations in ferromagnetic CoFeB, enabling the exploration of coherent phenomena in dense ferromagnetic ensembles.